Growing a Nature Kindergarten That Can Flourish. (20th July 2018) - Elliot, Enid; Krusekopf, Frances
Abstract: Growing a nature kindergarten that can flourish takes a community, careful planning, and sustained support. In 2011, the Sooke School District in British Columbia, Canada undertook the project of creating a nature kindergarten when outdoor programs of this kind did not exist in the Canadian public school system. Inspired by the well-established forest school and nature preschool models in northern Europe, a program to take 22 kindergarten students outside into nature every morning, regardless of the weather, was developed. This article explores how a unique framework and set of guiding principles were co-created by a diverse advisory committee. It also describes how the hiring, education, and ongoing support of the program's two educators — a kindergarten teacher and an early childhood educator — became critical to its success. The article offers an overview on steps taken, including how the idea was born, working within the public school system, building a framework and principles, hiring and education, preparing the educators, learning from our first year, ongoing support, and remaining questions. The authors' intention is not to articulate best practices, but to share key aspects of the program's development and implementation phases that allowed the nature kindergarten to thrive over the last 5 years.